Diagenesis and controls on reservoir quality of Lower Triassic red bed sandstones (Buntsandstein) from a marginal basin facies, southwest Germany. (August 2022) - Quandt, Dennis; Busch, Benjamin; Schmidt, Christina; Hilgers, Christoph
Abstract: After decades of hydrocarbon exploration and production in the Lower Triassic Buntsandstein from the Central European Basin center, the marginal southern German Buntsandstein has gained interest as a potential lithology for geothermal applications and lithium brine extractions. For this purpose and in order to better understand reservoir quality, porosity and permeability in combination with point-counted petrographic data of sandstones from SW Germany covering the Lower, Middle, and Upper Buntsandstein are studied. Textural, mineralogical, and petrophysical data show that the eolian and fluvial sandstones represent a heterogeneous reservoir system. Permeabilities vary over six orders of magnitude from 0.001 to 515 mD, while porosities are in the range of 7.9–21.5%. Different controls on reservoir quality exist. Large grain sizes ≥0.31 mm together with total quartz contents are the major controls on reservoir quality. Additional controls on reservoir quality are exerted by authigenic phases. Since porosity loss is dominated by compaction, the influence of authigenic clay phases on reservoir quality is minor. However, illite coatings on detrital quartz efficiently inhibited syntaxial quartz overgrowth. Where illite coatings lack, syntaxial quartz overgrowths locally stabilized the granular framework and, thus, preserved primary porosity. These authigenic phases, however, represent a local control, which cannot be applied on a regional scale. Similarly, enhanced secondary porosity due to feldspar dissolution is locally restricted and minor. The comparison with other studies on the Buntsandstein shows that its reservoir system is highly heterogeneous over small and large scales and within the same stratigraphic levels. In this study, quartz-rich and authigenic clay-poor sandstones with relative large grain sizes interpreted as eolian deposits reveal the best reservoir qualities. Highlights: Combined measured porosity and permeability, and point-counted petrographic data. Reservoir quality of one of the main geothermal reservoirs in south Germany. Besides minor controls, large grain size is the main control on reservoir quality. Interacting authigenic cements represent local/minor controls on reservoir quality. Buntsandstein is a heterogeneous reservoir system on spatial & stratigraphic scales.